Rasa Ini oleh Vierratale : Ketika Hati Bicara, Tapi Kata Tak Tersampaikan - Raudatul Jannah; Dwi Wahyu Candra Dewi (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This article discusses the lyrics of the song “Rasa Ini” by Vierratale as a representation of hidden feelings of love, emotional wounds, and doubts in relationships. Through a qualitative descriptive approach and Roland Barthes’ semiotic theory and Grice’s implicature theory, this article analyzes the figurative meaning in the song lyrics, especially the use of metaphor, symbolism, signs, connotation, denotation, and emotional narrative structures that emerge through a first-person perspective. The findings show that the lyrics of this song not only convey messages verbally, but also describe a strong inner mood through visualization of imagery, melody, musical nuances, and supporting poetic emotions. The presence of the background of the songwriter, Kevin Aprilio, also enriches the intertextual meaning that is manifested in the authenticity of emotions. This song is also a mirror of popular culture that reflects the dynamics of love in Indonesian society, especially love that is not conveyed directly, internalized in personal experiences, the psychology of the listener, and expressions of cultural identity.